Prediction of pathways of drug metabolism - Dickins, Maurice (Henry Stewart Talks, 2007)
Methods of in silico prediction based on substrates and DMEs, Computer based approaches, Predicting sites of metabolism, Predicting metabolic pathways, Mass spectroscopy for identifying metabolites
Reviewed at 2015/08/11